The response of grief to the repeat students in the sixth grade of middle school (Journal of the College of Basic Education, 2022)
The current research aims to identify the grief response among students repeaters in the sixth grade of middle school, and for the purpose of achieving the goal of the research, the researchers used the descriptive approach to achieve the goal of the research and for the purpose of conducting a statistical analysis of the grief response scale. The sample was chosen randomly in Anbar Governorate (Fallujah Education Department), and the researchers built a grief response scale and extracted the psychometric properties of the scale and used statistical indicators. In light of the research findings, the researchers recommended a set of recommendations and suggestions.